ASSESSMENT OF GEODIVERSITY AS TOOL FOR ENVIRONMENTAL MANAGEMENT OF PROTECTED NATURE AREAS IN SOUTH-EASTERN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The environmental management and nature protection policy in Latvia is mainly focused on biodiversity and protected species, while a geodiversity is ‘forgotten side’ of nature conservation work. Such situation is associated with an absence of a unified methodology for assessment of geodiversity, which is a shortened version of the term ‘geological and geomorphological diversity’. The concept of geodiversity, as well the quantitative assessment of abiotic nature values is successfully used in the last decade. However, it has not yet been applied in Latvia for purposes of environmental management. Considering that the aim of this study was to apply the methodology described in the scientific literature for the assessment of geodiversity index in the GIS environment. The estimating of geodiversity was performed in two protected nature areas in south-eastern Latvia, i.e. nature reserve “Pilskalnes Siguldiņa” and geological nature monument “Adamovas krauja”. The calculations of geodiversity index were done based on the components as geological data, landform units, morphogenetic processes, hydrological features and terrain roughness. The input data were processed, and numerical methods that analyze spatial data in regular grid format were applied in ArcGIS. The output data on the spatial variability of geodiversity index were reclassified in three classes in order to identify areas with low, medium and high geodiversity respectively. The assessment of geodiversity by quantifying the spatial distribution of geodiversity index can be used as a tool for environmental management of protected nature areas and spatial planning, allowing to identify places with high potential value and to prevent their transformations.